Endless scrolling through social media and work boredom: a dynamic spillover of information overload - Tathagata Bhowmik (Organization Management Journal)
Purpose – Based on the premise that young adults, as knowledge workers, are overstimulated by a constant bombardment of information from digital channels like social media, this paper aims to explore how the information overload, largely redundant and noisy, extracts cognitive resources from the workers without providing meaningful interaction, resulting in an aversive state of boredom characterized by a desire to engage in any meaningful activity but an inability to do so, both in their private and organizational lives. Design/methodology/approach – A review of the literature on boredom, focusing on the meaning and attention components (MAC) model of boredom is conducted to explain the phenomenon. This is followed by an exploration of information overload and the proposal of a dynamic spillover of boredom from the nonwork domains of workers to their organizational lives by integrating literature on work/life boundary spillover mechanisms. Findings – The propositions suggest that overstimulation and boredom are carried into their organizations by the workers. Research limitations/implications – The moderating effects of personality traits and organizational contexts like culture and digital infrastructure, which are outside the scope of this paper, can inform future research. Practical implications – The perilous ramifications of this spillover on both workers and their organizations are discussed, along with strategies for how organizations can help workers find meaning and purpose in their workspaces to reduce their propensity for boredom. Originality/value – This paper addresses and extends the limited research on the effects of information overload from social media on the organizational lives of knowledge workers.